농촌지역 인구이동：실태·요인·전망 - 김경덕 (한국농촌경제연구원, 2003)
Migration in the Rural Area: Current situation· Factors· Forecasting This paper analyzed the analysis of the inter-regional migration and forecasted the rural population by age, sex. In this paper, the degree of urbanization, PCMUR(percentage contribution of migration in urban population growth), elasticity of the degree of urbanization, and primary index was analyzed in the case of Korea. Furthermore, the regression analysis of net inter-regional migration and inter sector migration between the agriculture, and the industry and the service. Researcher : Kim Kyeong-Duk E-mail Address : kdkim@krei.re.kr
Keywords: 농촌인구